THE ROLE OF POSITRON EMISSION TOMOGRAPHY-COMPUTED TOMOGRAPHY (PET-CT) IN MEDICALLY REFRACTORY EPILEPSY (The Research of Medical Science Review, 2025)
Objective: To evaluate and compare the diagnostic accuracy of Magnetic Resonance Imaging (MRI) and Positron Emission Tomography-Computed Tomography (PET-CT) in localizing the epileptogenic zone in patients with drug- resistant epilepsy (DRE). Methods: From June to December 2024, 180 patients with DRE at Armed Forces Hospital, Rawalpindi, were cross-sectionally assessed using both MRI and PET-CT imaging. Using clinical and imaging consensus as the reference standard, we calculated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of both modalities. Chi-square analysis was used to assess statistical associations between imaging findings and clinical evaluation. Results: PET-CT demonstrated higher sensitivity (88.72%) and NPV (83.64%) compared to MRI (69.77% and 58.02%, respectively). PET-CT also showed greater diagnostic concordance (66.24%) than MRI (38.01%). When both imaging findings were concordant, the combined use of MRI and PET-CT achieved the highest diagnostic agreement (46.87%, p < 0.05); discordant or negative findings were associated with reduced diagnostic clarity. Conclusion: In DRE—especially in MRI-negative cases—PET-CT offers greater utility than MRI in identifying the epileptogenic zone. The combined use of both modalities enhances diagnostic accuracy and supports their integration into routine clinical evaluation of DRE.